2001
DOI: 10.1021/ol015798l
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Structure Determination, and Synthesis of Neodysiherbaine A, a New Excitatory Amino Acid from a Marine Sponge

Abstract: [structure: see text] A new excitatory amino acid, neodysiherbaine A (2), was isolated as a minor constituent of the aqueous extract from the marine sponge Dysidea herbacea. The structure was deduced by spectroscopic methods and established unambiguously by the total synthesis. The present synthesis, including as a key step cross-coupling of the 6/5-bicyclic core with an amino acid residue, is useful in constructing its structural analogues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
78
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 9 publications
1
78
0
Order By: Relevance
“…KARs agonists are known to be potent convulsants (Ben-Ari and Cossart, 2000), and DH, the first marine toxin isolated from D. herbacea, exhibits the most potent seizurogenic activity of any excitatory amino acid (Sakai et al, 1997). Most of the subsequent analogs of DH elicit varying degrees of convulsant behaviors; MSVIII-19, as an exception, produced subseizure-stereotyped behavior followed by unresponsiveness (Sasaki et al, 1999;Sakai et al, 2001a). 8,9-Epi-neoDH also fails to elicit convulsive behavior even at high doses, probably due to its very low affinity for KARs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…KARs agonists are known to be potent convulsants (Ben-Ari and Cossart, 2000), and DH, the first marine toxin isolated from D. herbacea, exhibits the most potent seizurogenic activity of any excitatory amino acid (Sakai et al, 1997). Most of the subsequent analogs of DH elicit varying degrees of convulsant behaviors; MSVIII-19, as an exception, produced subseizure-stereotyped behavior followed by unresponsiveness (Sasaki et al, 1999;Sakai et al, 2001a). 8,9-Epi-neoDH also fails to elicit convulsive behavior even at high doses, probably due to its very low affinity for KARs.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled chirality in the synthetic pathway for neoDH yielded two analogs of the marine toxin, 4-epi-neoDH and 2,4-epineoDH, in which the L-glutamate backbone in neoDH had altered stereochemistry (Sakai et al, 2001a) (Fig. 1); therefore, they seemed unlikely to bind KARs with significant affinity.…”
Section: C2 and C4 Epimers Maintain Affinity For A Subset Of Non-n-mementioning
confidence: 99%
See 1 more Smart Citation
“…The terrestrial excitotoxin acromelic acid, from the Japanese mushroom Clitocybe acromelalga, also falls into this structural class. More recent studies discovered two new natural iGluR ligands, dysiherbaine and neodysiherbaine A (Sakai et al 1997(Sakai et al , 2001a, underscoring the potential utility of screening marine benthic organisms for neuroactive molecules. These molecules are structurally distinct from the kainoids and thus constitute a third family of marine-derived ligands for ionotropic glutamate receptors.…”
Section: Fig 1 Chemical Structures Of Representative Iglur Ligands Dmentioning
confidence: 99%
“…In the course of the study we have isolated neodysiherbaine A [16], and several new betaines such as dysibetaine [17], dysibetaine PP, dysibetaine CPa and CPb [18], and demonstrated that this sponge is a rich source of novel amino acid derivatives of some biomedical interests. In this paper, we deal with isolation and structure elucidations of deoxynojirimycin derivatives: 1-deoxynojirimycin-6-phosphate (1) and its N-methyl derivative (2) from this sponge.…”
mentioning
confidence: 98%